Culture, Entrepreneurship, and Growth - Matthias Doepke; Fabrizio Zilibotti (Institute for the Study of Labor (IZA), 2013)
We discuss the two-way link between culture and economic growth. We present a model of endogenous technical change where growth is driven by the innovative activity of entrepreneurs. Entrepreneurship is risky and requires investments that affect the steepness of the lifetime consumption profile. As a consequence, the occupational choice of entrepreneurship hinges on risk tolerance and patience. Parents expecting their children to become entrepreneurs have an incentive to instill these two values in their children. Cultural transmission is Beckerian, i.e., parents are driven by the desire to maximize their children's happiness. We also consider, in an extension, a paternalistic motive for preference transmission. The growth rate of the economy depends on the fraction of the population choosing an entrepreneurial career. How many entrepreneurs there are in a society hinges, in turn, on parental investments in children's patience and risk tolerance. There can be multiple balanced-growth paths, where in faster-growing countries more people exhibit an entrepreneurial spirit. We discuss applications of models of endogenous preferences to the analysis of socio-economic transformations, such as the British Industrial Revolution. We also discuss empirical studies documenting the importance of culture and preference heterogeneity for economic growth.
Keywords: J20; O10; O40; 330; culture; entrepreneurship; innovation; economic growth; endogenous preferences; intergenerational preference transmission; Unternehmer; Wirtschaftskultur; Soziale Werte; Generationengerechtigkeit; Neue Wachstumstheorie; Theorie